FUNGSI PENGAWASAN DPRD TERHADAP KEPALA DAERAH DI KABUPATEN KLATEN TAHUN 2016 - Adhitana, ariya; astrika, Lusia; Harsasto, Priyatno (Journal of Politic and Government Studies, 2018)
ABSTRACTThis research entitled The Function of DPRD Supervision Performance Against Regional Head in Klaten District in 2016. This research is based on the number of cases concerning corruption, collusion, and nepotism that occurred in local government which involves the Head of Region as the main actors in it, so the role of DPRD as executive partners in conducting surveillance into the public spotlight.This study was conducted with the aim to find out how the function of DPRD oversight performance against the authority of the Regional Head. Using the qualitative approach, this case study is then researched through data collection techniques in the form of interviews and in-depth discussions with existing informants, ie DPRD members from 2014-2019. The data analysis is descriptively qualitatively described through data processing techniques with reduction, display and data verification.The results of this study indicate that the DPRD Klaten District has not implemented the function of supervision effectively because it does not meet the existing indicators in the form of productivity, quality, and also the growth of the DPRD institution itself. Therefore, the researcher has summarized the things that become obstacles for the DPRD Klaten district to be able to work effectively.The suggestion for the DPRD of Klaten district in order to realize the stability of the government is to improve the member performance of the council through quality improvement and resolve problems related to existing obstacles in the form of human resources and also political dynasties in Klaten district.Keyword: agency, supervision, DPRD, Head of Region.